HUBUNGAN KOMPETENSI LITERASI DIGITAL DENGAN HASIL BELAJAR GEOGRAFI DIKELAS X IPS SMA NEGERI 1 PAYAKUMBUH - reffakhri, dirga; Mariya, Sri (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
Abstract Competence comes from the word competence which describes the appearance of a certain ability in its entirety which is a dialectic (combination) between knowledge and ability. To be said to have digital literacy, one must master information, visual, media, and communication literacy. the amount of student literacy competence, how big is the achievement of student learning outcomes and the relationship between digital literacy competence and student learning outcomes. This research uses correlational quantitative. With a total sample of 94 students. Data collection with questionnaires, and documentation. The research instrument was tested with validity and reliability using the product moment correlation formula from Pearson and reliability testing with the Cronbach alpha formula. Data analysis used descriptive statistics of percentages and simple regression analysis. The results showed that the level of learning outcomes of students in class X IPS in SMA Negeri 1 Payakumbuh was in a fairly strong category, and there was a significant effect of digital literacy competence on the learning outcomes of students in class X SMA Negeri 1 Payakumbuh.